1997
DOI: 10.1016/s0006-3495(97)78316-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of geometrical parameters on synaptic transmission: a Monte Carlo simulation study

Abstract: Monte Carlo simulations of transmitter diffusion and its interactions with postsynaptic receptors have been used to study properties of quantal responses at central synapses. Fast synaptic responses characteristic of those recorded at glycinergic junctions on the teleost Mauthner cell (time to peak approximately 0.3-0.4 ms and decay time constant approximately 3-6 ms) served as the initial reference, and smaller contacts with fewer postsynaptic receptors were also modeled. Consistent with experimental findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 77 publications
(119 reference statements)
4
56
1
Order By: Relevance
“…Moreover, 2pEPSCs obtained from single synapses had low variability in 62% decay time (CV, 0.15), suggesting low variability of the clearance (Nusser et al, 2001). Actually, the reliability of NSFA was further improved by a slower diffusion constant of glutamate as confirmed by our simulation (data not shown), probably because of the increment of saturation level (Kruk et al, 1997).…”
Section: Kinetics Of 2pepscs In P3-p4 Pcssupporting
confidence: 54%
“…Moreover, 2pEPSCs obtained from single synapses had low variability in 62% decay time (CV, 0.15), suggesting low variability of the clearance (Nusser et al, 2001). Actually, the reliability of NSFA was further improved by a slower diffusion constant of glutamate as confirmed by our simulation (data not shown), probably because of the increment of saturation level (Kruk et al, 1997).…”
Section: Kinetics Of 2pepscs In P3-p4 Pcssupporting
confidence: 54%
“…Differences in these parameters in young and old neurons could be potentially responsible for the observed differential age-dependent inhibition by fast-off antagonists. However, although several studies have shown (at both excitatory and inhibitory synapses) that the neurotransmitter concentration peak and temporal profile critically depend on these parameters (Kleinle et al, 1996;Kruk et al, 1997;Barbour, 2001), much less is known about their developmental changes. When interpreting the data obtained from a simple model of cultured neurons, it is important to consider to what extent the developmental paradigm observed in vitro could reproduce that observed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…5B). Our finding that α7-nAChRs buffer the availability of ACh for binding to α3*-nAChRs suggests a role for spatial organization in determining intrinsic synaptic variability (18,23,25,30,38). A similar, cleft-limited diffusion buffering has been observed at snail synapses in culture where the extracellular glial-derived ACh binding protein modulates synaptic transmission by competing for released ACh (39,40).…”
mentioning
confidence: 88%
“…The source of mEPSC distribution variability has been attributed variously to the size of synaptic vesicles and the concentration of agonist in the cleft (25,30,36), the density of postsynaptic receptors (37), the release-site location or local environment (36), and the stochastics of receptor flickering (18). Our model CG is most sensitive to the number of ACh molecules released into the cleft, implicating vesicle size as the primary source of variability (see normalized derivative sensitivity above; Fig.…”
Section: Sensitivity Analysismentioning
confidence: 99%